REPRODUCTIVE BIOLOGY OF LANE SNAPPER, Lutjanus synagris (PERCIFORMES: LUTJANIDAE), OFF NORTHERN PERNAMBUCO STATE, BRAZIL - Viana, Daniel F.; Hazin, Fábio Hissa Vieira; Oliveira, P. G. (Arquivos de Ciências do Mar, 2015)
A total of 704 specimens of lane snapper, Lutjanus synagris , caught off Pernambuco State, Northeast Brazil, by small-scale artisanal fishing boats, were analyzed with regard to gonad maturation, gonadosomatic index, size at first sexual maturity, fecundity, and type and time of spawning. Of the sampled specimens, 364 were males and 340 females, resulting in a sex-ratio of 1.1 M : 1.0 F. Size at first sexual maturity was estimated at 16.4 cm TL for males and 17.1 cm TL for females. The monthly mean gonadosomatic index and the frequency of mature gonads suggest that the spawning season of the species in the studied region spans period from September to April. Absolute fecundity ranged from 30,870 to 59,280 oocytes.